2001
DOI: 10.1002/1521-3838(200112)20:5/6<395::aid-qsar395>3.0.co;2-#
|View full text |Cite
|
Sign up to set email alerts
|

Application of the Rough Set Theory in Structure Activity Relationships of Antielectrostatic Imidazolium Compounds

Abstract: The relationships between the chemical structure and the antielectrostatic effect of 180 imidazolium chlorides were analysed using the method of rough sets. The antielectrostatic activity was determined by measurements of the surface resistance. Using the rough sets approach the smallest set of condition attributes significant for high quality of classification has been found. The resulting decision rules describe relations between the structure and the antielectrostatic properties of imidazolium chlorides in … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2008
2008
2015
2015

Publication Types

Select...
4
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 9 publications
0
5
0
Order By: Relevance
“…In 2002, Krysinski et al followed up their earlier work by focusing on the ability of RST to provide decision rules which explain activity. 97 They studied the SAR of 180 antielectrostatic imidazolium compounds and showed that RST was able to explain much of the activity of the compounds using a reduced set of only four descriptors. They used the idea of strong decision rules (with high support) to eliminate many rules.…”
Section: Applicationsmentioning
confidence: 99%
“…In 2002, Krysinski et al followed up their earlier work by focusing on the ability of RST to provide decision rules which explain activity. 97 They studied the SAR of 180 antielectrostatic imidazolium compounds and showed that RST was able to explain much of the activity of the compounds using a reduced set of only four descriptors. They used the idea of strong decision rules (with high support) to eliminate many rules.…”
Section: Applicationsmentioning
confidence: 99%
“…Kobsa argued that most systems were based on the following categories of user data for personalization: demographic data, or "objective facts" about the user; user knowledge level; user skills and capabilities level; user interests and preferences; and user goals and plans (Kobsa et al, 2001). Brusilovsky (2001) suggested that user data should include the following user features that were used by personalized systems developed until 1996: the user's goals/tasks, knowledge, background, hyperspace experience, preferences, and interests. He went further and added user's individual traits to the list.…”
Section: Theoretical Backgroundmentioning
confidence: 99%
“…LC refers to the language learning conception. It is represented with the scales of the special questionnaire, which is revised to fit the situation of Chinese students by School of Foreign Language, Xi'an Jiaotong University, according to the research of Oxford (2001) and Wen and Wang (2004). (See Box 3).…”
Section: Definition 1 Personalitymentioning
confidence: 99%
See 2 more Smart Citations